Prison violence in Canada: A female inmate's perspective. - Croteau, Cathy. (University of Ottawa (Canada), 2000)
This study examines the issue of female prison violence in provincial correctional facilities in Canada. By examining this social issue through the inmate's perspective, this study attempts to identify what types of prison violence exist, explore possible explanations, examine the consequences, and formulate suggestions on how to reduce its occurrence. In conjunction with past results on prison violence, we selected the open ended interview as the form of research methodology. Fourteen women were interviewed for the purpose of this study, and for the scope of this Master's thesis we chose to explore the issue of violence between female inmates. Therefore, collective acts of violence and violence against correctional staff at the hands of the inmates were not the focus of this study. Instead, we chose to concentrate specifically on violence exclusively experienced between the female inmates. Seven women from two different correctional facilities in two provinces participated in this study. Although several women had served both federal and provincial sentences in their appropriate facilities, only the violence witnessed or participated within provincial facilities was considered. The study reveals that regardless of the limited amount of research, media recognition, and attention about female prison violence within provincial correctional facilities, it does exist. It also reveals that these women qualified violence using different criteria. Consequently, what some women may consider as milder forms of violence, others interpret the same acts of violence as more serious. Despite the women's interpretation of seriousness, the interviews in this study reveal that there are daily acts of violence amongst the women, and the intensity of that experience is individually defined. This research also concludes by recommending that more research is required in this area.
Keywords: Women's Studies.